Anesthetic Management of a Giant Ovarian Cyst: A Case Report - Indriani, Andi Riza Mirda; Saputra, T. Addi; Anggraeni, Novita (Journal of Health and Nutrition Research, 2025)
Ovarian cysts are highly prevalent among women, particularly those of reproductive age. However, giant ovarian cysts are rare, as most cases are detected early during routine gynecological or ultrasound examinations. A giant ovarian cyst is defined as an ovarian cyst that is more than 10 cm in diameter. Cases with giant size pose significant clinical challenges. We report a case of an 18-year-old female patient with symptoms of an enlarged abdomen for six months causing shortness of breath, difficulty in activities and supine position. Initial examination revealed an abdominal circumference of 120 cm and a large cystic mass that required laparotomy. Challenges in anesthetic management are related to increased abdominal pressure by the mass, including aspiration risk, hemodynamic disorders, supine hypotensive syndrome, and re-expansion pulmonary edema. Consideration of anesthetic agent selection and perioperative monitoring strategies is key to minimizing complications and ensuring patient safety. In this case, anesthetic agents were carefully selected due to the presence of a giant ovarian cyst that significantly increased intra-abdominal pressure. A balanced general anesthesia approach was employed, prioritizing agents with minimal cardiovascular effects to maintain hemodynamic stability. Propofol was chosen for induction because of its rapid onset and ease of titration, while sevoflurane was used for maintenance due to its favorable cardiovascular profile and rapid recovery characteristics. Rocuronium was administered to facilitate muscle relaxation, and fentanyl was selected for analgesia owing to its potency and minimal impact on hemodynamics. To mitigate the risk of aspiration, rapid sequence induction was performed with endotracheal intubation in a semi-recumbent position. This anesthetic strategy was specifically tailored to address the risks associated with large intra-abdominal masses, such as aspiration, cardiovascular instability, and respiratory compromise.